2004
DOI: 10.1128/mcb.24.19.8477-8486.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Keap1-BTB Protein Is an Adaptor That Bridges Nrf2 to a Cul3-Based E3 Ligase: Oxidative Stress Sensing by a Cul3-Keap1 Ligase

Abstract: The Nrf2 transcription factor promotes survival following cellular insults that trigger oxidative damage. Nrf2 activity is opposed by the BTB/POZ domain protein Keap1. Keap1 is proposed to regulate Nrf2 activity strictly through its capacity to inhibit Nrf2 nuclear import. Recent work suggests that inhibition of Nrf2 may also depend upon ubiquitin-mediated proteolysis. To address the contribution of Keap1-dependent sequestration versus Nrf2 proteolysis, we identified the E3 ligase that regulates Nrf2 ubiquitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
703
0
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 869 publications
(716 citation statements)
references
References 32 publications
9
703
0
4
Order By: Relevance
“…One of these siRNA, Target1, has been shown to increase Nrf2 protein in HaCaT keratinocyte cells, resulting in up-regulation of endogenous human antioxidant genes and an elevation in intracellular GSH. While the present study was being undertaken, two groups reported using plasmid-delivered short hairpin RNA against mouse Keap1 in 293T cells to demonstrate that Keap1 functions as an adaptor protein for the ubiquitination of Nrf2 by the Cul3-Roc1 ligase (21,22). In neither instance, however, was the effect of RNA interference on the expression of endogenous target genes investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these siRNA, Target1, has been shown to increase Nrf2 protein in HaCaT keratinocyte cells, resulting in up-regulation of endogenous human antioxidant genes and an elevation in intracellular GSH. While the present study was being undertaken, two groups reported using plasmid-delivered short hairpin RNA against mouse Keap1 in 293T cells to demonstrate that Keap1 functions as an adaptor protein for the ubiquitination of Nrf2 by the Cul3-Roc1 ligase (21,22). In neither instance, however, was the effect of RNA interference on the expression of endogenous target genes investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Humans possess 51 proteins containing both BTB͞POZ and Kelch repeat domains; Keap1 is a member of subclass 1 (19). Keap1 controls the half-life of Nrf2 by acting as a substrate adaptor protein for the cullin 3-Roc1 ubiquitin E3 ligase (20)(21)(22). Under homeostatic conditions, Keap1 promotes degradation of Nrf2 via the 26S proteasome, but this activity is lost during redox stress.…”
mentioning
confidence: 99%
“…Nrf2 localizes in the cytoplasm in the absence of an activator, though a small fraction of Nrf2 mediates constitutive transcription of a number of target genes in the nucleus in uninduced cells. The cytoplasmic Nrf2 forms a complex with Keap1, which functions as a key regulator of Nrf2 [10,13,15,16]. According to this model, Keap1, a cytoplasmic protein, sequesters Nrf2 in the cytoplasm and serves as a substrate adaptor, bringing Nrf2 to the cullin 3 (Cul3) dependent E3 enzyme that catalyzes the ubiquitination of the Nrf2 protein.…”
Section: Introductionmentioning
confidence: 99%
“…By binding to the 5=-upstream regulatory antioxidant response element (ARE) regions of cytoprotective genes, Nrf2 upregulates their transcription [2,3], thus protecting cells against damage by reactive oxygen intermediates or other electrophilic species [4]. Keap1 functions as a bridge between Nrf2 and the Cullin3-based E3-ligase ubiquitination complex, promoting ubiquitination and subsequent proteasomal degradation of Nrf2 [5][6][7], thus preventing nuclear accumulation of Nrf2. Without the intervention of Keap1, levels of Nrf2 are elevated in the nucleus causing upregulation of the ARE [8].…”
mentioning
confidence: 99%